Induction of Enzymes Associated with Lysigenous Aerenchyma Formation in Roots of Zea mays during Hypoxia or Nitrogen Starvation. - He, C. J. (1994)
Either hypoxia, which stimulates ethylene biosynthesis, or temporary N starvation, which depresses ethylene production, leads to formation of aerenchyma in maize (Zea mays L.) adventitious roots by extensive lysis of cortical cells. We studied the activity of enzymes closely involved in either ethylene formation (1-amino-cyclopropane-1-carboxylic acid synthase [ACC synthase]) or cell-wall dissolution (cellulase). Activity of ACC synthase was stimulated in the apical zone of intact roots by hypoxia, but not by anoxia or N starvation. However, N starvation, as well as hypoxia, did enhance cellulase activity in the apical zone, but not in the older zones of the same roots. Cellulase activity did not increase during hypoxia or N starvation in the presence of aminoethoxyvinylglycine, an inhibitor of ACC synthase, but this inhibition of cellulase induction was reversed during simultaneous exposure to exogenous ethylene. Together these results indicate both the role of ethylene in signaling cell lysis in response to two distinct environmental factors and the significance of hypoxia rather than anoxia in stimulation of ethylene biosynthesis in maize roots.